A randomised, patient-assessor blinded, sham-controlled trial of external non-invasive peripheral nerve stimulation for chronic neuropathic pain following peripheral nerve injury (EN-PENS trial): study protocol for a randomised controlled trial. Issue 1 (December 2016) - Johnson, Selina; Goebel, Andreas; Richey, Roberta; Holmes, Emily; Hughes, Dyfrig
Abstract Background Eight percent of people in the UK are estimated to have persistent (chronic) neuropathic pain, and for many there is no effective treatment. Medications are the most common first-line treatment but often have limited benefit or adverse events. Surgical treatments, such as spinal cord stimulation, are then often considered. External non-invasive peripheral nerve stimulation (EN-PENS) is a form of electrical stimulation that involves placing a pen-shaped electrode onto the skin, which can be easily self-administered by patients. Observational studies suggest that EN-PENS may relieve pain for people with localised neuropathic pain; however, there is currently no evidence from controlled trials to confirm the efficacy and confidently determine the effect size for patients with longstanding neuropathic pain. Methods EN-PENS is a single-site, blinded, randomised controlled parallel-group superiority add-on trial with a 1:1 allocation ratio, designed to evaluate the efficacy of treatment versus control treatment in 76 patients with longstanding neuropathic pain following peripheral nerve injury. Patients with moderate to -severe neuropathic pain following peripheral nerve injury will be randomised to receive either the active or control treatment, followed by an optional treatment extension or treatment switch to the alternative treatment arm. The primary outcome is average 24-h pain intensity recorded on an 11-point (0–10) numerical rating scale, averaged over the last 7 days of treatment. Discussion Study results will be used to inform potential treatment efficacy and cost-effectiveness of EN-PENS for this population group. Trial registration ISRCTN53432663 . Registered on 7 July 2016.